Implementasi Sistem Perhitungan Produksi Bahan Baku Plastik Berbasis Android - Nurdiana Handayani; Dian Adi Prastiyo; Rohmat Taufiq; Hendra Mayatopani (Universitas Islam Lamongan, 2022)
The production calculation system is carried out before the production process of plastic raw materials is carried out. The process is done to find out the amount of production based on purchase orders in a company. Often the occurrence of loss or frame of data in the production calculation process because it is still in the form of document archives and untidy scheduling processes. Research is intensively conducted, detailed to find out the problems that occur in the process of calculating plastic raw materials through the process of approaching study cases in the company to produce user requirments specifications and system design. In connecting user incomprehension regarding technical and clarifying the specifications of the user's desired needs in the software development process using prototype methods. Android-based plastic raw material production calculation system in order to help in the production process and scheduling process that is in accordance with the order. Keyword: Production Calculation System, User Requirments Specification, Prototype, Android.